The Role of The Internal Audit Unit in the Indonesia Civil Pilot Academy Public Service Agency - Yasyfa' Kawakibi; Hery Susanto (RSF Press, 2024)
The Indonesia Civil Pilot Academy Public Service Agency is an educational institution under the Ministry of Transportation. A Public Service Agency is responsible for managing finances and budgets effectively and efficiently. A unit that supports the effectiveness of the Public Service Agency’s financial management is the Internal Audit Unit. This research examines the role of the Internal Audit Unit in improving financial efficiency at the Public Service Agency of the Indonesia Civil Pilot Academy. The method used is qualitative research with a field study approach. Data were collected through interviews, observation, and document study. The research included interviews with three participants who are directly involved with the Indonesia Civil Pilot Academy’s finances: the Head of The Internal Audit Unit, The Expenditure Treasurer, and The Program and Activity Plan Analyst. The research results show that internal unit audit plays an important role in the Public Service Agency of the Indonesia Civil Pilot Academy. The internal audit unit can ensure that the use of Public Service Agency funds is carried out effectively and efficiently, as well as maintaining accountability and compliance with laws and regulations. Results suggest that a competent and well-communicating Internal Audit Unit is vital for optimal financial management.